Analisis Struktur dan Nilai Konservasi Beberapa Puisi pada Antologi Puisi Bersiap Menjadi Dongeng - Muhammad Noor Ahsin (Aksara: Jurnal Bahasa dan Sastra, 2017)
Poetry as a kind of literary holds many mysteries and deep meaning. It is not only a beautiful word, poetry is also a medium of expression and also conservation especially in literature. Poetry anthology Bersiap Menjadi Dongeng creation Mukti Sutarman Espe from Keluarga Penulis Kudus (KPK), the reader can find a lot of symbols and meanings and conservation elements of literature and also the Holy culture is very strong. The strength of these values makes the writer interested to study it. This research was conducted with the analysis of the inner structure.The sampling technique used purposive sampling or data collection techniques based on specific objectives. Data collection techniques used is to examine the document. Data analysis techniques used in this study are interwoven analytical techniques which include three components: data reduction, data presentation, and conclution data. The final result of this research is in the form of an inner structure analysis of some poems and cultural conservation values is very strong in the poetry anthology Bersiap menjadi Dongeng.